Understanding the Role of Humic Acids on Crop Performance and Soil Health - Ampong, Kwame; Thilakaranthna, Malinda S.; Gorim, Linda Yuya (Frontiers in agronomy, 2022)
Humic acids (HA) are organic molecules that play essential roles in improving soil properties, plant growth, and agronomic parameters. The sources of HA include coal, lignite, soils, and organic materials. Humic acid-based products have been used in crop production in recent years to ensure the sustainability of agriculture production. Reviewed literature shows that HA can positively affect soil physical, chemical, and biological characteristics, including texture, structure, water holding capacity, cation exchange capacity, pH, soil carbon, enzymes, nitrogen cycling, and nutrient availability. This review highlights the relevance of HA on crop growth, plant hormone production, nutrient uptake and assimilation, yield, and protein synthesis. The effect of HA on soil properties and crops is influenced by the HA type, HA application rate, HA application mode, soil type, solubility, molecular size, and functional group. This review also identifies some knowledge gaps in HA studies. HA and its application rate have not been tested in field experiments under different crops in rotation, nitrogen fertilizer forms, sites and climatic conditions. Furthermore, HA chemical and molecular structures, their water and alkaline soluble fractions have not been tested under field experiments to evaluate their effects on crop yield, quality, and soil health. The relationship between soil-plant nutrient availability and plant nutrient uptake following HA application should also be further studied.